Selection interview skills - Seven Dimensions (Firm) (Australia : Seven Dimensions, 2008)
Contains an outstanding series of 12 video programs for learning interviewing skills to ensure the manager select the best applicants
episode 1. Body language & rapport in interviewing - episode 2. Question types in interviews - episode 3. Office manager interview - episode 5. Interviewing for receptionist - episode 6. Sales rep interview - episode 7. Property manager interview - episode 8. Assessment centre interviews - episode 10. Role plays & work tests - episode 11. interviewing panels - episode 12. Reference check
Keywords: Employment interviewing; Employee selection